Human T-Cell Lymphotropic Virus Type 1 Subtype C Molecular Variants among Indigenous Australians: New Insights into the Molecular Epidemiology of HTLV-1 in Australo-Melanesia - Cassar, Olivier; Einsiedel, Lloyd; Afonso, Philippe V.; Gessain, Antoine (PLOS Neglected Tropical Diseases, 2013)
Author Summary The Human T-lymphotropic virus type 1 (HTLV-1) infects at least 5–10 million persons worldwide. In Oceania, previous studies have shown that HTLV-1 is present in a few ancient populations from remote areas of Papua New Guinea, the Solomon Islands, the Vanuatu archipelago and central Australia. The latter comprise one of the most socio-economically disadvantaged groups within any developed country. Characterization of the few available HTLV-1 viruses from Oceania indicates that these belong to a specific HTLV-1 genotype, the Australo-Melanesian c-subtype. In this study, we provide details for 23 HTLV-1 viruses derived from the Indigenous population of central Australia, a vast remote area of 1,000,000 km2. We reveal considerable genetic diversity of HTLV-1c subtype viruses and the existence of two HTLV-1c clades within which a high degree of genetic diversity was also apparent. These newly described HTLV-1c clades clustered according to the geographic origin of their human hosts. Indigenous Australians from the North of central Australia harbor HTLV-1c subtype viruses that are distinct from those of individuals from regions to the South. These data suggest that HTLV-1 was probably introduced to Australia during ancient migration events and was then confined to isolated Indigenous communities in central Australia.